Strategi Optimalisasi Pemasaran Desa Wisata Purwabakti Melalui Penggunaan Media Sosial The Optimization strategy of Social Media Use in Purwabakti Tourist Village - Yudha, Aditya Prima; Andrianto, Nizam Mohammad; Wihartika, Doni; Luluatin, Zomrotul Mariam; Xavieranisa, Najwa; Purnama, Indah (Penerbit Widina, Widina Media Utama, 2024)
Bogor is one of the regions in West Java Province that has a lot of tourist potential for visitors. A total of 10.6 million tourists visited Bogor Regency throughout 2023. This figure represents a 25% increase from the previous year, which was approximately 8 million in 2022. Tourist villages are currently becoming a trendy alternative for tourism, promoting the concept of interaction between nature, culture, and local communities. According to information from the Department of Culture and Tourism of Bogor Regency, there are currently 70 potential tourist villages in the Bogor Regency area that will be developed, spread across 40 sub-districts. Purwabakti Village is one of the potential tourist villages in the Bogor Regency area that offers the beauty of hilly landscapes, rice fields, rivers, and local wisdom. This potential is not accompanied by the number of tourists visiting. The level of tourist visits in the Purwabakti tourist village is still very low. This is because the community is not yet aware of the tourism potential of the Purwabakti tourist village. The managers of the Purwabakti tourist village have not yet optimized their digital marketing. The Purwabakti tourist village's management has yet to effectively leverage the available social media platforms. This is evident from the small and inconsistent number of content posts, as well as the low number of followers. The Instagram social media account is also not yet connected to other marketing platforms such as the website and WhatsApp Business. The community service activities carried out resulted in a flagship tourism package in Purwabakti village, specifically a trekking and camping package in the Riung Kawung area. Riung Kawung is an area in the Purwabakti tourist village that features many Kawung trees, is located by the river, and has open land that can be used as a camping area. The tour package is published on the website and social media Instagram under the name